αDβ2 as a novel target of experimental polymicrobial sepsis - Koutsogiannaki, Sophia; Hou, Lifei; Okuno, Toshiaki; Shibamura-Fujiogi, Miho; Luo, Hongbo R.; Yuki, Koichi (Frontiers in Immunology, 2022)
Since sepsis was defined three decades ago, it has been a target of intensive study. However, there is no specific sepsis treatment available, with its high mortality and morbidity. αDβ2 (CD11d/CD18) is one of the four β2 integrin members. Its role in sepsis has been limitedly studied. Using an experimental polymicrobial sepsis model, we found that the deficiency of αDβ2 was associated with less lung injury and better outcome, which was in sharp contrast to other β2 integrin member αLβ2 (CD11a/CD18), and αMβ2 (CD11b/CD18). This phenotype was supported by a reduction of bacterial loads in αDβ2 knockout mice. Further analysis showed that the deficiency of αDβ2 led to a reduction of neutrophil cell death as well as an increase in neutrophil phagocytosis in both murine and human systems. Our data showed a unique role of αDβ2 among the β2 integrin members, which would serve as a potential target to improve the outcome of sepsis.